Product-Type Operators from Hardy Spaces to Bloch-Type Spaces and Zygmund-Type Spaces. (27th July 2022) - Guo, Zhitao; Liu, Linlin
Abstract: The boundedness and compactness of a class of product-type operators T ψ 1, ψ 2, φ n from Hardy spaces to (little) Bloch-type space and (little) Zygmund-type space are characterized in this article. Meanwhile, we also estimate the norm of T ψ 1, ψ 2, φ n .